Aseptic technique training and infection-risk reduction practices among healthcare workers: A quasi-experimental study in Kwara State, Nigeria - Isiaq, Abdulmuhit Temitope; Akorede, Seun Nurudeen; Biu, Adamu Abdulkareem; Sanusi, Muhammad (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2026)
Healthcare-associated infections (HAIs) remain a persistent burden in resource-limited health systems, yet evidence on structured, sustained aseptic technique education for healthcare workers (HCWs) in Nigerian tertiary hospitals is still limited. This study aimed to determine the effect of a six-week aseptic technique training on HCWs’ work-related infection-risk reduction practices in tertiary hospitals in Kwara State, Nigeria. A quasi-experimental pre-test/post-test design with experimental and control groups was used. Seventy (70) nurses and medical laboratory scientists were recruited from two tertiary hospitals, which were randomly assigned to intervention or control sites using a fishbowl technique. Data were collected using a researcher-developed questionnaire rated on a Likert scale with high internal consistency (α = 0.895). The experimental group received a six-week aseptic technique education programme, while the control group received no intervention. Paired and independent samples t-tests were applied. Findings indicated a significant improvement in the experimental group’s practices (pre-test mean = 2.47, post-test mean = 3.68; t = 27.96, p < 0.001; Cohen’s d = 4.73), and a significant post-test difference between experimental (mean = 3.68) and control groups (mean = 2.41; t = 23.90, p < 0.001; Cohen’s d = 5.70). These results support institutionalising mandatory, practical, and reinforced training within Infection Prevention and Control (IPC) policies, aligned with family health protection and Islamic ethical values of cleanliness, harm prevention, and communal responsibility, to sustain safer care and reduce infection risks.